Population density of Elaeidobius kamerunicus Faust and abiotic factors effect within anthesising inflorescences of Malaysian oil palm - Zulkefli, Muhamad Haziq Hadif; Jamian, Syari; Adam, Nur Azura; Abdullah, Sumaiyah; Mohd Masri, Mohamed Mazmira; Moslim, Ramle; Mohamad, Saharul Abillah (Penerbit Universiti Kebangsaan Malaysia, 2024)
Elaeidobius kamerunicus is an important pollinator in Malaysian oil palm cultivation. After four decades of introduction, there are still reports of low fruit set for oil palm planted on mineral and peat soil areas in Malaysia. A comprehensive report on the population density of the weevil within the anthesising days with regard to Malaysia's climate is still lacking. Thus, this study aimed to elucidate the E. kamerunicus population density during anthesising days at both male and female inflorescence of oil palm by investigating the predominant soil affected with low fruit set, namely mineral and peat soil. The study was conducted from July 2022 to June 2023. At female inflorescence, the E. kamerunicus population was assessed by setting up a yellow sticky trap daily from 1st to 4th day of anthesis. On male inflorescence, the weevil population was assessed by counting the E. kamerunicus present on the spikelet from 1st to 5th day of anthesis. Correlation between abiotic factors and the E. kamerunicus population was analysed using statistical software. On the female inflorescence, anthesising day revealed a significant difference (P<0.01) in the weevil population density per inflorescence. Further analysis indicates no significant difference between the 1st and 2nd-day female anthesis in the E. kamerunicus population and the highest visitation on 1st day of anthesis. The abiotic factor did not influence the weevil population on peak anthesising days. The E. kamerunicus population density per spikelet and per inflorescence were significantly different (P<0.01) between anthesising days at male inflorescence. Further analysis between the 3rd-day anthesis and other days indicates significant differences, with the highest population congregation on the 3rd day. During peak population density on male inflorescence, the temperature depicted a significant, negative and weak relationship with the E. kamerunicus population. The female E. kamerunicus was observed highest at both inflorescences compared to the male E. kamerunicus. This study provides comprehensive evidence of higher population density of the weevil on a specific day of anthesis and can be used as a reference to monitor the E. kamerunicus pollination activity.